Indian Corporate Social Responsibility: From philanthropy to assessing the sustainability of business and society - Gilormini, Patrick (Management and Administration Journal, 2024)
India Corporate Social Responsibility (CSR) has undergone significant changes in thepast three years. Their driving factors are regulations and financial institutions requirements: theNational Voluntary Guidelines on Social, Environmental & Economic Responsibilities of Business[2011], the Security Exchange Board of India clause 55 [2012] and the New Company Act section135 [2013]. Indian CSR appears essentially about what is done with corporation profits. It meansengaging directly with local communities, identifying their basic needs and integrating them withbusiness goals. The top major themes area for Indian CSR initiatives are community welfare,education, health care and rural development. This chapter presents the historical tradition of CSRas corporate philanthropy in India. After a presentation of the new legal framework and recentinstitutional developments, it analyses their implication on CSR reporting and organizational challengesfor Indian companies especially SMEs.